The mediating effect of psychological well-being on self-efficacy and career development of physical education major students - Yikeranmu Yiming; Rong Ma; Yalikun Saiyidu (BMC Psychology)
Abstract We investigated the association between self-efficacy and career exploration and career adaptability of students majoring in physical education via psychological well-being because these students undergo a critical phase during their career exploration because of an inclination towards reevaluating reality, realising their thoughts, and developing early professional goals. We used a primary data set collected from universities in two provinces of China. The participants were students with a major in physical education (n = 1381; age = 18-22 years). Students participated in the study by signing an informed consent. Hayes PROCESS model was used to apply multiple mediation model. The results suggest that higher self-efficacy is associated with better career exploration and career adaptability. In addition, four components of psychological well-being played a significant mediating role, and those are self-acceptance, positive relationship with others, personal growth, and purpose in life. The findings suggest that self-efficacy and psychological well-being are predominantly advantageous for the career development of Chinese students enrolled in the field of physical education.